Biodiesel from municipal sewage sludge (MSS): Challenges and cost analysis. Issue 4 (3rd April 2017) - Demirbas, Ayhan
ABSTRACT: Municipal sewage sludge (MSS) comes from wastewater treatment plant. Sewage sludge is a waste formed during treatment of wastewater. Wastewater sludge contains a variety of organic and inorganic compounds. The sewage sludge contains mainly lipids, proteins, sugars, detergents, and phenols. Sewage sludge also includes toxic and hazardous organic and inorganic pollutants sources. The MSS contains a significant amount of lipid fraction characterized as oils, greases, fats, and long-chain fatty acid originating from domestic and industrial sludge. The MSS contains a low density of lipids. Activated MSS is a potential source of biodiesel. The MSS is subjected to the pretreatment processes before lipid extraction. The optimum production of biodiesel is faced with huge challenges. The main challenges are collecting the sludge, separating lipids, microbial processing, optimum production of biodiesel and product separation, soap formation, maintaining product quality, bioreactor design, economics of biodiesel production, and regulatory concerns. A major economic factor to consider with respect to the input costs of biodiesel production is the price of the feedstock, which is about 80% of the total operating cost. Other important costs are the labor cost and the price of methanol and catalyst that must be added to the feedstock. The high value of vegetable oils as food products make the production of a cost-effective fuel very challenging.